Singing the Gospel : Lutheran hymns and the success of the Reformation - Brown, Christopher Boyd, 1972- (Harvard historical studies, 2005)
This book offers a new appraisal of the Reformation and its popular appeal, based on the place of German hymns in the sixteenth-century press and in the lives of early Lutherans. The Bohemian mining town of Joachimsthal--where pastors, musicians, and laity forged an enduring and influential union of Lutheranism, music, and culture--is at the center of the story.